Sequences of two related multiple antibiotic resistance virulence plasmids sharing a unique IS26-related molecular signature isolated from different Escherichia coli pathotypes from different hosts. - Carola Venturini (Public Library of Science (PLoS), 2013)
Enterohemorrhagic Escherichia coli (EHEC) and atypical enteropathogenic E. coli (aEPEC) are important zoonotic pathogens that increasingly are becoming resistant to multiple antibiotics. Here we describe two plasmids, pO26-CRL125 (125 kb) from a human O26:H- EHEC, and pO111-CRL115 (115kb) from a bovine O111 aEPEC, that impart resistance to ampicillin, kanamycin, neomycin, streptomycin, sulfathiazole, trimethoprim and tetracycline and both contain atypical class 1 integrons with an identical IS26-mediated deletion in their 3´-conserved segment. Complete sequence analysis showed that pO26-CRL125 and pO111-CRL115 are essentially identical except for a 9.7 kb fragment, present in the backbone of pO26-CRL125 but absent in pO111-CRL115, and several indels. The 9.7 kb fragment encodes IncI-associated genes involved in plasmid stability during conjugation, a putative transposase gene and three imperfect repeats. Contiguous sequence identical to regions within these pO26-CRL125 imperfect repeats was identified in pO111-CRL115 precisely where the 9.7 kb fragment is missing, suggesting it may be mobile. Sequences shared between the plasmids include a complete IncZ replicon, a unique toxin/antitoxin system, IncI stability and maintenance genes, a novel putative serine protease autotransporter, and an IncI1 transfer system including a unique shufflon. Both plasmids carry a derivate Tn21 transposon with an atypical class 1 integron comprising a dfrA5 gene cassette encoding resistance to trimethoprim, and 24 bp of the 3´-conserved segment followed by Tn6026, which encodes resistance to ampicillin, kanymycin, neomycin, streptomycin and sulfathiazole. The Tn21-derivative transposon is linked to a truncated Tn1721, encoding resistance to tetracycline, via a region containing the IncP-1α oriV. Absence of the 5 bp direct repeats flanking Tn3-family transposons, indicates that homologous recombination events played a key role in the formation of this complex antibiotic resistance gene locus. Comparative sequence analysis of these closely related plasmids reveals aspects of plasmid evolution in pathogenic E. coli from different hosts.